2015
DOI: 10.1038/nchem.2395
|View full text |Cite
|
Sign up to set email alerts
|

A threading receptor for polysaccharides

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms A threading receptor for polysaccharides Polysaccharides are the dominant organic molecules in the biosphere 1 , and thus key renewable resources 2,3 . However the most abundant, including cellulose and chitin, are generally the most difficult to utilise due to extreme insolubility. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 31 publications
(30 reference statements)
3
92
0
Order By: Relevance
“…Such an analysis can indeed be informative, as it has been often reported that carbohydrate binding in water with inflexible cages is driven substantially by entropy. [17,18] For the specific case of amino saccharides with CB [7], our earlier experiment [25] suggested that entropy participated importantly (ÀTDS/DG % 35 %) in the binding of GalN and GluN, for which the anomer discrimination is more dramatic than for ManN. This substantial entropic contribution is also consistent with recent experimental binding data for polysaccharides with synthetic lectins, [18] for which it was reported that entropy sometimes contributed more to the binding than enthalpy.…”
Section: Decomposition Of Binding Free Energiessupporting
confidence: 81%
“…Such an analysis can indeed be informative, as it has been often reported that carbohydrate binding in water with inflexible cages is driven substantially by entropy. [17,18] For the specific case of amino saccharides with CB [7], our earlier experiment [25] suggested that entropy participated importantly (ÀTDS/DG % 35 %) in the binding of GalN and GluN, for which the anomer discrimination is more dramatic than for ManN. This substantial entropic contribution is also consistent with recent experimental binding data for polysaccharides with synthetic lectins, [18] for which it was reported that entropy sometimes contributed more to the binding than enthalpy.…”
Section: Decomposition Of Binding Free Energiessupporting
confidence: 81%
“…To the best of our knowledge, this is the highest affinity that has been measured for a biomimetic receptor binding a small, electrically neutral monosaccharide derivative in water. Receptor 9 also showed good affinities for GlcNAc 14 (10 times higher than 4 )4e and methyl β‐ d ‐glucoside ( 15 ; 5 times higher than the previous record) 4a. Surprisingly, α‐GlcNAc derivative 13 , with an axial OMe group, was also bound fairly strongly.…”
mentioning
confidence: 77%
“…In 4 , the hydrophobic surfaces are provided by biphenyls, which are readily introduced and provide adequate CH–π interactions. However, biphenyls are prone to twisting, which disrupts contact with axial CH groups, while condensed aromatic compounds are planar 4a,4b. A 1,3,6,8‐tetrasubstituted pyrene is geometrically equivalent to the biphenyls in 4 , so tricyclic cage 5 was identified as a promising design.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 ), and have yielded encouraging results. Selectivities are good, and some affinities are above 10 4   m −1 , even for uncharged substrates 9a,9b. However, the selectivity for all‐equatorial carbohydrates is a constraint on potential applications, as many substrates of interest do not belong to this family.…”
mentioning
confidence: 99%